Pancreatic ductal adenocarcinoma in a patient with pancreas divisum and gastrointestinal duplication cyst: a case report - Naoto Takahashi; Hiroyuki Nitta; Akira Umemura; Hirokatsu Katagiri; Shoji Kanno; Daiki Takeda; Kenji Makabe; Satoshi Amano; Masao Nishiya; Noriyuki Uesugi; Tamotsu Sugai; Akira Sasaki (Surgical Case Reports)
Abstract Background The complication of duplication of alimentary tracts and pancreas divisum (PD) is a rare malformation and the development of pancreatic ductal adenocarcinoma (PDAC) in this malformation is also extremely rare. There have been some reports of complication of malignancy in a gastric duplication cyst (GDC) and PD. However, there have been no reports of complication of PDAC in cases with GDC and PD. Case presentation A 54-year-old woman was followed up at the previous hospital due to a history of ovarian endometrial adenocarcinoma. She also had a surgical history of partial excision for a GDC and pancreatic tail of PD in her childhood. A gynecological follow-up computed tomography (CT) examination revealed the pancreatic body tumor and the bifurcated main pancreatic duct dilatation. Furthermore, magnetic resonance cholangiopancreatography also revealed that the ventral main pancreatic duct communicated with the GDC. The initial levels of tumor markers were high, but we could not achieve preoperative histopathological diagnosis. The preoperative diagnosis was PDAC occurring in a case with PD and GDC. She received two courses of neoadjuvant chemotherapy with gemcitabine and nab-paclitaxel. A CT examination after neoadjuvant chemotherapy revealed the shrinkage of the tumor, and then we performed distal pancreatectomy with splenectomy and GDC resection. A histopathological examination revealed invasive PDAC and lymph node metastases; pathological staging was T1N1M0, stage III. Furthermore, PD and GDC were also histopathologically detected. The postoperative course was uneventful, and she was discharged on the postoperative day 25. She received S-1 monotherapy for 6 months, and no recurrence has been detected at 1 year after radical resection. Conclusions We herein presented an extremely rare combined case of PD, GDC and PDAC. We successfully treated it by neoadjuvant chemotherapy and distal pancreatectomy with GDC resection, and postoperative chemotherapy.